Disturbances of Normal Intestinal Microflora in Children and a Modern Approach to their Correction - Muhammadiyevich, Haydarov Musomiddin (American Journal of Biomedicine and Pharmacy, 2025)
Although dysbacteriosis is a well-recognized clinical and laboratory syndrome, its interpretation can be problematic [17]. Therefore, in addition to the ability to correctly interpret the nature of the microbial landscape in real practice, the ability of the practicing pediatrician to analyze the premorbid background, the nature of nutrition and food tolerance, as well as to understand the nature of the general somatic problem in its specific clinical variants, is of great importance. To date, it has been established that the human microflora has a very large biological potential, sufficient both to ensure the full protection of the host and to provide its metabolic support [6,12,18]. The indigenous microflora plays a very important role in the processes of digestion and metabolism. There is a lot of direct and indirect evidence that intestinal microorganisms, due to the production of various enzymes (proteases, amylases, lipases, etc.), enhance the hydrolysis of proteins, ferment carbohydrates, saponify fats, prevent bacterial decarboxylation of food histidine, and inhibit the increase in histamine levels [1,13]. A number of studies have provided convincing evidence of the amylase and caseinolytic activity of bifidobacteria and lactobacteria, their participation in the metabolism of bile acids, as a result of which the total pool of the latter is maintained during enterohepatic circulation [10].